Preterm Life in Sterile Conditions: A Study on Preterm, Germ-Free Piglets - Splichalova, Alla; Slavikova, Vera; Splichalova, Zdislava; Splichal, Igor (Frontiers in Immunology, 2018)
Preterm infants born with immature organ systems, which can impede normal development, can also be highly sensitive to different biological and/or environmental factors. Animal models could aid in investigating and understanding the effects of different conditions on the health of these immunocompromised infants. The epitheliochorial placentation of the pig prevents the prenatal transfer of protective colostral immunoglobulins. Surgically-derived colostrum-deprived piglets are free of maternal immunoglobulins, and the cells that are normally provided via colostrum. We bred preterm germ-free piglets in sterile conditions, and compared them with their term counterparts. Enterocyte development and intestinal morphology, tight junction proteins claudin-1 and occludin, pattern-recognizing receptors, adaptor molecules and coreceptors (RAGE, TLR2, TLR4, TLR9, MyD88, TRIF, MD2, and CD14), and inflammasome NLRP3 transcription were all evaluated. The production of inflammatory mediators IFN-, IL 4, IL-6, IL-8, IL-10, IL 12/23 p40, TNF-, IFN-, and HMGB1 in the intestine of germ-free piglets was also assessed. In the preterm germ-free piglets, the ileum showed decreased lamina propria cellularity, reduced villous height, and thinner and less distinct stratification - especially muscle layer, in comparison with their term counterparts. Claudin-1 transcription increased in the intestine of the preterm piglets. The transcription levels of pattern-recognizing receptors and adaptor molecules showed ambiguous trends between the groups. The levels of IL-6, IL-8, IL-10, and TNF- were increased in the preterm ileum numerically (though not significantly), with statistically significant increases in the colon. Additionally, IL-12/23 p40 and IFN- were statistically significantly higher in the preterm colon. Both blood plasma and intestinal HMGB1 levels were nonsignificantly higher in the preterm group. We propose that the intestine of the preterm germ-free piglets showed “mild inflammation in sterile conditions”. This model, which establishes preterm, hysterectomy-derived germ-free piglets, without protective maternal immunoglobulins, can be used to study influences of microbiota, nutrition and therapeutic interventions on the development and health of vulnerable immunocompromised preterm infants.